VOCATIONAL HIGH SCHOOL STUDENTS' ABILITY TO SOLVE WORD PROBLEMS IN THE TOPIC OF LINEAR EQUATIONS SYSTEM WITH TWO VARIABLES - Putri Miftaakhul Jannah; Sri Rejeki (FKIP Universitas Muhammadiyah Tangerang, 2023)
Problem-solving is a mathematical skill that students need to develop to solve challenges in everyday life. However, this ability has yet to be fully mastered by students. Therefore, this study analyzes the problem-solving skills of ten-grade private Vocational High School students in Sragen, Central Java, Indonesia, particularly in the Linear Equations System with Two Variables (LESTV). This study used a descriptive qualitative method involving 25 Computer and Network Engineering students (CNE). The problem-solving indicators used are understanding the problem, devising a plan, carrying out the plan, and looking back. This study grouped students into three levels based on the results of the Mid Semester Assessment (MSA) of students' initial abilities, namely low, medium, and high initial ability levels. Based on the analysis, this study indicates that students with low initial ability levels are less able to understand problems and the other stages. Students with a moderate level of initial ability can meet the indicators of understanding the problem and devising a plan. Students with a high level of initial ability fulfill all problem-solving indicators. Students have been able to understand problems, devise a plan, carry out the plan, and look back. Students with a high level of initial ability can analyze and conclude the results of the answers correctly, accompanied by re-examining the solutions they have obtained.